Zakat Management Optimization in Maqashid Al-Shariah Perspective: A Study on BAZNAS in Bondowoso Regency - Mas’ud Mas’ud (UAS PRESS, 2022)
Zakat and infaq institutions play a strategic role in addressing socio-economic challenges and improving the welfare of underprivileged communities. Through professional and accountable governance, official bodies such as the Badan Amil Zakat Nasional (BAZNAS) are expected to strengthen the institutional management of zakat. This study examines how BAZNAS of Bondowoso Regency optimizes its role in fostering a smart, healthy, and economically competitive society. It focuses on strategies implemented in the fields of education, health, and economic empowerment. This research employs a qualitative field-based approach. Data were collected through observation, in-depth interviews, and document analysis to assess the effectiveness of zakat programs in poverty alleviation. The findings indicate that zakat distribution in Bondowoso Regency is structured around three primary models: productive, consumptive, and empowerment-based assistance. Productive zakat includes business tools and capital support; consumptive zakat provides direct aid to highly vulnerable beneficiaries; and empowerment-based zakat supports scholarships, medical assistance, and social welfare initiatives. These programs are implemented through the Smart, Healthy, and Empowered Bondowoso initiatives. Overall, BAZNAS Bondowoso Regency demonstrates a strategic approach to sustainable zakat governance aimed at promoting community independence and socio-economic resilience.